Bridging Marketing and Finance: A Systematic Review of the Strategic Brand Risk and Firm Value Nexus - Vivi Indah Bintari; Ratih Hurriyati; Puspo Dewi Dirgantari; Dexi Triadinda (Eastasouth Institute, 2026)
This study systematically reviews and synthesizes the relationship between strategic brand risk and firm value by bridging marketing and finance perspectives within the emerging marketing and finance nexus. It explores how brand related risks evolve from traditional marketing concerns into strategic financial assets that influence firm valuation and investor trust. Following the PRISMA 2020 guidelines, a Systematic Literature Review (SLR) was conducted using the Watase UAKE platform integrated with Scopus. 47 peer reviewed articles published between 2015 and 2024 were analyzed through bibliometric mapping (VOSviewer 1.6.20) and thematic content analysis to identify dominant theories, constructs, and causal mechanisms linking brand risk and firm value. Findings reveal a paradigm shift from customerbased brand equity to strategic brand risk management, emphasizing sustainability signaling and corporate legitimacy. The literature is grounded in five key theories: Stakeholder Theory, Signaling Theory, Brand Equity Theory, ResourceBased View, and Legitimacy Theory. The relationship between brand risk and firm value is primarily indirect mediated by CSR engagement, corporate reputation, and consumer trust, and moderated by sustainability orientation and strategic brand innovation. Theoretically, this study enhances understanding of brands as financial instruments that mitigate market volatility and signal corporate integrity. Methodologically, it integrates bibliometric and thematic approaches to capture the longitudinal evolution of cross disciplinary research. Practically, it provides insights for CMOs and CFOs to design risksensitive brand strategies that enhance investor confidence and shareholder value.